Fear of movement in patients after lumbar spine fusion and an analysis of factors: a cross-sectional study - Pan, Yingyan; Qi, Qiong; Yang, Chao; Dai, Meng; Zhang, Huihui; Wen, Jie; Qiu, Hailing (Frontiers in Neurology, 2025)
BackgroundNumerous studies have confirmed the significant benefits of exercise rehabilitation in both preoperative and postoperative treatment of lumbar disc herniation. However, there is a prevalent fear or avoidance of exercise among patients with chronic low back pain prior to surgery, while research on exercise fear after lumbar fusion remains insufficient. This study aims to investigate the incidence and severity of exercise fear in patients with chronic low back pain and leg pain following lumbar fusion surgery, as well as analyze its underlying mechanism and associated risk factors.MethodsA cross-sectional study was conducted on patients undergoing posterior lumbar fusion for lumbar disc herniation between May 2023 and January 2024. The Tampa Motor Phobia Scale (TSK-17) was utilized to assess motor fear among participants. Additionally, clinical and imaging risk factors were analyzed through multivariate regression analysis to determine relevant influencing factors.ResultsFollowing strict inclusion and exclusion criteria, a total of 178 patients who underwent posterior lumbar fusion were included in this study, comprising 104 males (58.4%). Kinesiophobia was defined as a TSK-17 score ≥ 37, which identified 65.2% (116/178) of the screened patients exhibiting motor phobia. Multivariate regression analysis revealed that motor phobia was strongly associated with age, higher levels of pain intensity, elevated Beck Depression Inventory (BDI) scores, lower General Self-Efficacy Scale (GSES) scores, increased number of surgical levels involved during operation, greater amount of postoperative incision drainage, higher degree of nerve root compression observed on preoperative lumbar MRI scans, as well as smaller area occupied by the paravertebral muscles in the lumbar region.ConclusionThis study has identified a significantly high incidence of postoperative exercise fear in patients undergoing posterior lumbar fusion, along with potential risk factors. Therefore, it is crucial for clinicians to closely evaluate and monitor these patients in order to develop appropriate strategies for postoperative exercise rehabilitation.